METHOTREXATE IN THE MANAGEMENT OF MODERATE TO SEVERE ATOPIC DERMATITIS - SAEED, S; SAEED, M; ASLAM, S; LIAQAT, Z; DAWOOD, N; SAFDAR, OM (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Dermatology from June 2021 to June 2022 to analyze the complication profile, adverse effects, and efficacy of methotrexate in patients with moderate to severe AD. The patients with moderate to severe AD were included in the study. The demographic data, clinical records, and response to MTX were analyzed. The clinical response was assessed as a decrease in itching, improvement in skin lesions, lesser use of topical CS, and assessment by the dermatologist. During the treatment, the patient's renal function, liver function, and complete blood count were assessed every month for three months. The study was conducted on 40 patients (17 female, 23 male). The mean starting dose was 13.8mg. The mean maintenance dose was 17.8 mg. The dose was gradually tapered after control of symptoms. 28 (70%) patients had clear responses, 7 (17.5%) had excellent, 3 (7.5%) had good, and 2(5%) patients had partial response. The mean duration of MTX therapy was 36.9 months. Due to disease control, MTX was discontinued in 8 (17.5%) patients. 4 (10%) patients remained clear, and treatment was restarted in 3 (7.5%) patients due to flare. Thirty-two patients were still on treatment at the time of the study. Nausea occurred in 4(10%) patients, fatigue in 3 (7.5%) and a transient increase in transaminases in 7 (17.5%) patients. 1 (2.5%)patient had a transient decrease in hemoglobin and platelet level; Hb was maintained at 106-120 g/L, and platelet level became normal. Methotrexate is safe and effective for the treatment of moderate to severe AD. Lower doses can control disease in the long term without posing any significant risks.